Current primary health care practices and research challenges in Latin America - Yavich, Natalia (2016)
Since the eighties, most Latin American (LA) countries experienced important social and health improvements as well as profound socio-epidemiological and cultural changes. During this period, the Primary health care (PHC) has been at the core of many reforms. The reforms, with different levels of success, tried to shift from a selective PHC approach to a comprehensive PHC approach. In this context PHC was called upon to address a wider range of problems including the long-standing challenges of still-uncontrolled infectious diseases and maternal-child health, other previously-overlooked problems, such as chronic diseases, traffic accidents, social and domestic violence, mental and oral health, and problem drug use and emerging problems such as HIV, H1N1 and Zika virus. This article presents a special issue of the Family Practice: the International Journal for Research in Primary Care that addresses central challenges of PHC in the LA Region. This issue includes studies from 13 countries of LA. There are two groups of articles: one that tackles analysis of quality and effectiveness of PHC in different health systems, services and programs and a second group made up of studies that analyze the political, institutional and organizational determinants of the PHC development.While the articles joint by this issue along with the existent body of PHC have produced significant scientific contributions, PHC research in LA is still limited and insufficiently guided by the countries' priorities, rules and its health systems and population characteristics.